An Assessment of Pawpaw Leaf Meal as Protein Ingredient for Finishing Broiler - Onyimonyi, A.E.; Ernest, Onu (International Journal of Poultry Science, 2009)
A feeding trial was conducted to evaluate the effect of dietary inclusion of Pawpaw Leaf Meal (PLM) on the performance of finishing broilers. Sixty 5 weeks old broilers were used for the study that lasted for 28 days. The sixty birds were assigned to four dietary treatments with fifteen birds per treatment in a Completely Randomized Design. Each treatment was replicated thrice. Four isonitrogenous and isocaloric broiler finisher diets containing 21% CP and 2800kcalME/kg were formulated. PLM was incorporated at levels of 0.5, 1.5 and 2.0% in treatments 2, 3 and 4 respectively. Treatment 1 had no PLM and was used as the control diet. Results should that the effect of treatments on final body weight, weight gain, daily weight gain, feed conversion ratio and feed cost/kg gain were significant (P<0.05). Birds on treatment 4 had a final body weight of 2972.5 g which differed significantly (P<0.05) from the 2612.5, 2785.0 and 2875.0 g observed for birds on T1, T2, and T3 respectively. The same birds on treatment 4 gained significantly (P< 0.05) more weight of 2044.0 g during the study period. A feed cost/kg gain of N138.42 was also recorded for the birds on T4 as against N167.28, N148.15 and N141.05 observed for birds on T1, T2 and T3 respectively. Percentage of edible cuts as represented by dressing percentage was also significantly (P<0.05) higher in the birds on T4. The meat of birds on T4 also had a significantly (P<0.05) general acceptability. It is concluded that a 2% inclusion of PLM in the diet of finishing broilers could improve performance, carcass and organoleptic indices.